Mapping Organization determinants of Work Performance - Infante-Rejano, Eduardo (ANDULI, Revista Andaluza de Ciencias Sociales, 2024)
The purpose of the present research was to identify and assess key organizational factors affecting work performance via Gilbert´s Behavioral Engineering Model (BEM). Therefore, a self-made scale considering BEM´s dimensions was developed and tested. Data were gathered from the 1st of April to end of May 2023, using a randomly stratified sample of 297 Mexican companies of Sonora State. The final questionnaire – named ADOPT- proved adequate psychometric properties to assess eight organizational factors of human performance proposed. ADOPT liability and validity are shown in the light of commented literature and data on present organizational effectiveness and corporate longevity. Main results indicate a global alpha scale liability of .92 being Task Support, knowledge/Competences, and Context most valued predictors of organizational effectiveness, followed by Aims/Objectives and Feedback factors. It was also confirmed that both contextual (environmental level) and behaviour (individual level) type of supports are equally important in predicting work performance. Evidence indicate that organizational performance management in SMEs is highly achieved on a long-term basis by attending these key factors in a specific loop, i.e. contextualising, system maintenance (feedback), and empowering. This sequence support personnel assessments as essential for empowering decision-making processes.